Diversi Bagi Anak Pelaku Tindak Pidana Kejahatan yang Jatuhan Pidananya Diatas 7 Tahun - Yukhanid Abadiyah; Iskandar Wibawa (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Diversion is a critical mechanism in the juvenile criminal justice system in Indonesia, aimed at protecting the rights of children and preventing the negative impacts of formal criminal proceedings. This normative legal study explores the challenges and potential improvements in implementing diversion for juvenile offenders facing sentences over 7 years. The study utilizes secondary data sources, including the Indonesian Juvenile Criminal Justice System Law (Law No. 11 of 2012), Supreme Court Regulation No. 4 of 2014 on Diversion Guidelines, and relevant literature on restorative justice and child protection. The analysis reveals significant barriers, such as legal limitations, cultural factors, and inconsistencies with international standards like the Beijing Rules. The study concludes with recommendations for revising existing legislation to remove the 7-year sentence limitation, enhancing coordination among legal and rehabilitation institutions, providing restorative justice training for law enforcement, and increasing public awareness of the importance of diversion and child rights protection. These steps are essential for ensuring a more just and effective implementation of diversion in Indonesia.